Clinical and immunological spectrum of MHC class I deficiency: insights from a long-term cohort with two novel mutations - Haskologlu, Sule; Ikinciogullari, Aydan; Islamoglu, Candan; Bal, Sevgi Kostel; Bayrakoglu, Deniz; Erdem, Serife; Karahan, Zeynep Ceren; Ardeniz, Omur; Aytekin, Caner; Heper, Aylin; Ceylaner, Serdar; Dogu, Figen (Frontiers in Immunology, 2025)
BackgroundMajor histocompatibility complex (MHC) Class I deficiency is a rare form of primary immunodeficiency that typically presents with recurrent sinopulmonary infections, bronchiectasis, and granulomatous skin lesions during late childhood or adolescence.MethodsThis retrospective study describes the clinical, immunological, and long-term follow-up data of 11 patients diagnosed MHC Class I deficiency.ResultsThe cohort included 11 patients (6 males, 5 females) with a median age of 26 years (range 19–44). The median age at diagnosis was 19 years, with a diagnostic delay of 14 years. Bronchiectasis was seen in 10 patients, granulomatous skin lesions in 6, uveitis in 5, and nasal septum perforation in 3. All but one patient survived during a median follow-up of 11 years. HLA-ABC expression ranged from 0% to 73%, with persistently low mean fluorescence intensity (0.4–3.8). IgM levels were reduced in 7 patients. Ten patients were persistently positive for anti-rubella IgM, including all six with granulomatous skin lesions. Immunophenotyping revealed reduced CD3+ (n=2), CD4+ (n=3), CD8+ (n=3), CD19+ (n=5), CD3−CD16+CD56+ (n=3), CD19+ IgM-27+ IgD- (switched memory B cells) (n=7), and CD19+ IgM-27+ IgD+ (marginal zone B cells) (n=8). All patients had elevated γδ+ T cells, and NK cells were reduced in three. Seven patients had TAP1 and four had TAP2 mutations, with no significant genotype–phenotype differences.ConclusionMHC Class I deficiency presents a broad clinical spectrum from asymptomatic to life-threatening disease. Granulomatous tissue damage and uveitis contributed to morbidity. Persistent rubella-specific IgM in most patients, including those without granulomas, is a novel serologic finding that may reflect altered antiviral immunity. Its clinical significance remains uncertain and, further studies with tissue-based viral detection are needed to clarify this observation.